1965
DOI: 10.1063/1.1714514
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Reactions in Silicon Web-Dendrite Crystals

Abstract: The origin and reactions of dislocations in silicon web-dendrite crystals are discussed. In particular, x-ray topographs are compared with etching results. Dislocations having [21̄1̄] axes or 〈110〉 type axes have been characterized. In the former case, normal edge and 20° dislocations are seen; however, an apparently new dislocation with a [21̄1̄] axis and [101] type or [110] type of Burgers vector has also been observed. Dislocations having a [11̄0] axis and [110] Burgers vector have been identified and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1966
1966
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In our web, the majority of dislocations were generated in bursts at melt e n t r a p m e n t centers on the dendrite surfaces (4,7). In our web, the majority of dislocations were generated in bursts at melt e n t r a p m e n t centers on the dendrite surfaces (4,7).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In our web, the majority of dislocations were generated in bursts at melt e n t r a p m e n t centers on the dendrite surfaces (4,7). In our web, the majority of dislocations were generated in bursts at melt e n t r a p m e n t centers on the dendrite surfaces (4,7).…”
Section: Discussionmentioning
confidence: 53%
“…Dec. 15, 1970. This was Paper 513 presented at the Montreal Meeting of the Society, Oct. [6][7][8][9][10][11] 1968.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The defect structure was previously investigated by etching and x -r a y topographical techniques (5,6). This paper reports on an extensive investigation by electron microscopy using a high voltage transmission electron microscope (accelerating voltage V = 1 MV) and a scanning electron microscope (V = 1 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Wilhelm and Joshi (639) reported that fault planes in steam oxidized silicon appeared to be due to oxygen induced precipitation along faults producing strain displacement fields which give rise to dislocations during the steam oxidation treatment. The origin and reactions of dislocations in silicon and germanium were discussed by O'Hara (438) and O'Hara and Schwuttke (439). The effects of dislocation interactions in silicon were made visible by the peculiar etching characteristics of the dislocations involved.…”
Section: Crystals Glasses and Ceramicsmentioning
confidence: 99%